Pembelajaran di Era Pandemi Covid 19 pada Sekolah Dasar di Kabupaten Minahasa Tenggara - Pistos Manila (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to describe the learning process in the Covid 19 pandemic era at the Southeast Minahasa Regency Elementary School. By using qualitative research methods. Where the respondents were elementary school teachers in Southeast Minahasa Regency. Based on the data recorded from this study, it was found that: in general there are types of media used in the learning process, namely: Android cellphones and modules, student worksheets (LKS), the learning process is carried out in two methods, namely: online (in the network) and offline (outside the network) or guling (mobile teacher), the assessment process is carried out in writing which is given questions to students and is done at home, in general the outcomes of students are quite good, average above 75%, even exceeding normality, and it was also found that there were a number of supporting factors in the learning process, including: availability of cellphones, provision of data pulses, positive responses from parents, while inhibiting factors, among others, not all students had Android phones, the network is often disrupted, data pulses run out there are a number of parents who are less able to teach their children, parents' attention/care is still less/ not maximized